Clonal relationship between multidrug-resistant Escherichia coli ST69 from poultry and humans in Lusaka, Zambia. Issue 21 (14th January 2022) - Shawa, Misheck; Furuta, Yoshikazu; Paudel, Atmika; Kabunda, O'Brian; Mulenga, Evans; Mubanga, Maron; Kamboyi, Harvey; Zorigt, Tuvshinzaya; Chambaro, Herman; Simbotwe, Manyando; Hang'ombe, Bernard; Higashi, Hideaki
Abstract: Multidrug-resistant (MDR) Escherichia coli in food animals such as chickens is an emerging public health concern in Zambia. Additionally, the country's high demand for poultry products necessitates further investigation into the link between poultry and human MDR E . coli . Twenty cefotaxime-resistant E. coli isolates collected from poultry in Lusaka, Zambia, were screened for multidrug resistance and sequenced on MiSeq and MinION platforms. Genomes were assembled de novo and compared with 36 previously reported cefotaxime-resistant E. coli isolates from inpatients at the University Teaching Hospital, Lusaka. All (20/20, 100%) poultry isolates exhibited resistance to ampicillin, chloramphenicol and doxycycline. Phylogenetic analysis and hierarchical clustering showed a high degree of genetic relatedness between E. coli O17:H18-ST69 from poultry and humans. The E. coli O17:H18-ST69 clone accounted for 4/20 (20%) poultry- and 9/36 (25%) human-associated isolates that shared two plasmids harboring 14 antimicrobial resistance (AMR) genes. However, comparison analysis showed that the isolates also had other AMR plasmids distinct for each niche. Our results suggested clonal transmission of MDR E. coli between poultry and humans, with the potential acquisition of niche-specific AMR plasmids. Thus, the control of MDR E. coli requires a One Health approach involving both human and animal health sectors. Abstract : This study reports the clonal relationship of multidrug-resistant Escherichia coli between poultry and humans in Zambia.